Simulation modeling of bunchy top epidemics in a changing climate - Raymundo, Avelino D. (Journal of Environmental Science and Management, 2011)
Epidemics of bunchy top, the most destructive viral disease of abaca and banana in the Philippines, were modeled using STELLA veersion 9.1, a modeling software appropriate for systems analysis of biological populations. A previously developed coupled model of the population dynamics of the insect vector Pentalonia nigronervosa and epidemic progress of the bunchy top disease was improved and modified by incorporating the effects of temperature. Both insect vector and bunchy top epidemic submodels followed the H-L-S-R (healthy (h) - latent (L) - infections (S) - removed (R) epidemic modeling approach where the diseased plants or insects population was partitioned into nonoverlapping compartments or states. The modified model satisfactorily simulated P. nigronervosa population dynamics and bunchy top epidemics. The effect of climate change on bunchy top epidemics was simulated through the addition of I and 29 degree celcius to the average monthly temperature from 1998-2007 in Davao City, Philippines. The increase in monthly average temperatures of 1 and 2 degree celcius reduced the simulated bunchy top epidemics as the rates of increase in the number of viruliferous aphids and disease incidence were reduced, and epidemic onset was delayed.